Dampak Kesadaran Keberlanjutan dalam Fashion terhadap Niat Membeli: Variabel Mediasi Komitmen Keberlanjutan - Putri, Cherryll Heryono; Rosa , Audrey Dhamara Elysia (APPS Publications, 2023)
This study addresses the urgency of climate change by examining the impact of sustainability awareness on the fashion industry. Amid a rising green market, driven by environmental concerns and consumer awareness, the fashion industry grapples with its environmental footprint, particularly in fast fashion. Millennials and Gen Z show a strong preference for ecologically sustainable products. The research aimed to bridge inconsistencies in existing studies regarding the relationship between sustainability awareness and the intention to purchase sustainable fashion items. Utilizing the Theory of Planned Behavior, the study surveyed 107 respondents using Google Forms and a 5-point Likert scale. Then using the results, validity and reliability, collinearity, model summary, and hypothesis are tested. Findings reveal a positive connection between sustainability awareness, commitment, and purchase intention, with commitment mediating the awareness-intention relationship. Theoretical implications align with previous research, while managerial implications emphasize the importance of sustainability education, commitment-building, and innovative sustainable product development to meet evolving consumer preferences.